Radiofrequency catheter ablation of macroreentrant ventricular tachycardia after corrective surgery for tetralogy of Fallot. Issue 4 (4th April 2014) - Chinushi, Masaomi; Saitou, Osamu; Furushima, Hiroshi
Abstract: Ventricular tachycardia (VT) may occur in patients after corrective surgery for tetralogy of Fallot (ToF), and this can be a cause of sudden cardiac death. Macroreentrant VT is a unique mechanism in these patients, although other mechanisms are involved in VT development. Owing to advances in electrophysiological knowledge and medical technology, macroreentrant VT after corrective surgery for ToF can be treated by catheter ablation. In the macroreentrant circuit of VT, several critical isthmuses (types 1–4) could be included, and these are supported by anatomical obstacles and operative interventions in the right ventricle. Linear radiofrequency (RF) application through the critical isthmus can terminate and prevent the recurrence of macroreentrant VT. Among the critical isthmuses, the type 1 isthmus (between the right ventricular outflow scar and tricuspid annulus) is the most common, but compared with the other types of isthmuses, it is longer so and has a thicker myocardium. Therefore, higher‐energy RF application using irrigation and/or large‐tip ablation catheters is usually required to complete the linear conduction block. Since other isthmuses may simultaneously work as critical components of the macroreentrant circuit, detailed mapping is encouraged before starting RF application in the type 1 isthmus. Since long‐term evidence of the effectiveness of catheter ablation for VT in patients after ToF repair is limited, hybrid treatment with implantable cardioverter defibrillators (ICDs) would be a reasonable strategy for secondary prevention of cardiac events, such as that in patients with other underlying heart diseases. Indications of electrophysiological study, catheter ablation, and/or ICD therapy for primary prevention of sudden cardiac death should be further examined in high‐risk patients after ToF repair.